An empirical investigation of the SMS Exam Result Query System Model (SERQSM) in Malaysia : the case of Universiti Malaysia Sabah - Hanudin, Amin; Mohammad Rizal Abdul Hamid Suddin Lada, (Sunway University College, 2008)
The introduction of mobile phones has provided many benefits to business leaders, government agencies and to the public at large. Today, most of the universities in Malaysia are using mobile phones to help in communicating with their students. By using mobile phones, students are able to send and retrieve information in relation to their examination results, information on tuition fees and others university matters. This paper aims to explore the factors that influence university students to use ?SMS Exam Result Query System? (SERQS). This study was conducted in one of the public Universities in Malaysia: Universiti Malaysia Sabah. In order to explore the factors, the current study will extend the applicability of ?technology acceptance model? in the context of SERQS. This paper provides a workable direction for the University in offering many services using mobile phone communications for students.